Consequences of the COVID-19 Pandemic on Child Justice Systems - Foussard, Cédric; De Klerk-Pérez Cruz, Mariana; Virgil, Angela (European Integration Studies, 2023)
The COVID-19 pandemic, declared a global health emergency in 2020, presented unique challenges for child justice systems worldwide. Children in detention facilities faced increased health risks, prompting efforts to expedite their release and protect their well-being. The pandemic disrupted normal legal proceedings, making it difficult for legal professionals, judges, and authorities to maintain contact with children in the justice system. In response, some countries introduced safety measures during court hearings, such as physical barriers, to protect children from the virus. Others turned to digital technology, conducting remote hearings to reduce the risk of viral transmission. While digitalization offers efficiency and cost-effectiveness, questions regarding fair access to justice and data security have arisen. This article explores the potential long-term impact of digital justice on child justice systems beyond the pandemic. The pandemic’s effects on children in detention, their rights in crisis situations, the roles of child justice professionals, and the adoption of virtual courts are discussed, highlighting the evolving landscape of child justice post-pandemic.